The genome sequence of the blonde ray, Raja brachyura Lafont, 1871 [version 1; peer review: 2 approved] - Patrick Adkins; Rachel Brittain; Kesella Scott-Somme (Wellcome Open Research, 2024)
We present a genome assembly from an individual female Raja brachyura (Blonde Ray; Chordata; Chondrichthyes; Rajiformes; Rajidae). The genome sequence spans 2,700.50 megabases. Most of the assembly is scaffolded into 49 chromosomal pseudomolecules, including the X sex chromosome. The mitochondrial genome has also been assembled and is 17.12 kilobases in length. Gene annotation of this assembly on Ensembl identified 24,252 protein-coding genes.